If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + y = 110 Solving 2x + y = 110 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1y' to each side of the equation. 2x + y + -1y = 110 + -1y Combine like terms: y + -1y = 0 2x + 0 = 110 + -1y 2x = 110 + -1y Divide each side by '2'. x = 55 + -0.5y Simplifying x = 55 + -0.5y
| (Y-6)-(y+6)=7y | | Y=ln(e^7x) | | 4x-10=-60-10x | | 41-5x=14-8x | | x+(x*0.28)=100 | | 10+6x=-15+x | | 3x-9=x+27 | | Ln(x-3)= | | -(-1k+1)=-5(1-6k)+7k | | b+3=3 | | y-9=-17 | | 4.8x+38.3=10.9-8.9x | | 1/3x-5/6=1/9x | | sqrt(2x^2-5x-3)=x+1 | | 15x^2+3x= | | x+sqrt(25-x^2)=7 | | 5y*2y-3= | | x^2+sqrt(25-x^2)=7 | | 2(x+1)+3x+6=4 | | 15x-7=-2 | | t^2+4t+3=0 | | 28=2x+2 | | 3lnx^6-2lnx^2=14 | | 3ln(x^6)-2ln(x^2)=14 | | 3x-9x+5x-7x= | | cos^2x-sen^2x=0 | | 0.025p-2=0.15(p-5) | | 2.1d+18=216(d+8) | | z*8+(3-i)*z*4-3*i=0 | | 5v+3=7 | | 2q-4+8q=yq-8+3q | | 3b-(1-2b)= |